Factors contributing to severe early childhood caries in south-west Germany - Bissar, Abdul-Razak; Schiller, Peter Johannes; Wolff, Anna; Niekusch, U.; Schulte, Andreas G. (Clinical oral investigations, 2014)
The purpose of this study is to investigate the contribution of selected variables to the occurrence of severe early childhood caries (S-ECC) in 3- to 5-year-old kindergarten children.